Kebijakan Kepala Madrasah dalam Pengelolaan Ekstrakulikuler Pencak Silat Pagar Nusa di SMA Boarding School Darussalamah Tahun Ajaran 2024/2025 - SYIFA'UDIN WAHID (UNISAN JURNAL, 2025)
This journal analyzes the policy of the headmaster in managing the extracurricular activity of Pencak Silat Pagar Nusa at Darussalamah Boarding School for the academic year 2024/2025. As an Indonesian traditional culture and sport, Pencak Silat holds significant value in character building for students. Appropriate policies in managing this extracurricular activity are expected to enhance student engagement, talent development, and academic and non-academic achievements. Data shows that the effective implementation of extracurricular activities contributes to increased discipline and student responsibility (Suhardjo, 2022). This research employs a qualitative method with in-depth interviews with the headmaster, coaches, and students. The conclusion of this study indicates that participatory and contribution-based policies play a significant role in the successful implementation of Pencak Silat in schools.